Pengaruh Kepemilikan Institusi, Debt To Equity Terhadap Net Profit Margin Perusahaan Pada Indeks JII70 - Moch Ridho Ghazali Rahman (AkMen JURNAL ILMIAH, 2022)
The purpose of this study is to determine the effect of institutional ownership structure, Debt to Equity ratio, on Return On Equity on the JII70 index. The research data was generated by taking data from the Indonesia Stock Exchange which was selected purposively to be the sample in this study. All studies were analyzed through smart PLS with two stages of analysis, namely bootstrapping analysis to assess the level of significance or probability of research data and research hypotheses. The results of this study indicate that if institutional ownership has a direct effect on firm value, Debt to Equity has a direct effect on firm value.